(untitled) (Training and Practice : Journal of Educational Sciences, 2022)
In the last two years, the pandemic has subverted almost every area of life. The changes also had a significant impact on the educational sector. Following the first wave of the epidemic, certain measures were introduced in primary, intermediate and higher education, some of which were similar, while others were completely different. Universities had used several platforms even before the pandemic. In spite of this, the mandatory relocation of the lessons into the online platforms proved to be a challenge for both students and teachers. At the sports organizer faculty of ELTE, theoretic lessons were carried out online in synchronous and asynchronous forms. The students experienced the pros and cons of both forms. After all, concerning learning experience, synchronous online lessons were considered more effective.